Peran Media Sosial Terhadap Akhlak Siswa Kelas IX di Pondok Pesantren Babussalam Desa Teluk Bakung Kecamatan Tanjung Pura - Putri Patmawati; Ahmad Sanusi Luqman; Nurmisda Ramayani (STIKes Ibnu Sina Ajibarang, 2023)
The role of social media for class IX students at the Babussalam Modern Islamic Boarding School is used as an important means of supporting student learning so that the benefits felt by students are quicker to understand the content of the learning material provided and students' insight into the subject matter is broader. Teachers still set limits for students when using social media so that their use can be effective and avoid misuse by just playing with social media. The morals of class IX students at the Babussalam Modern Islamic Boarding School show good morals in activities at the Babussalam Modern Islamic Boarding School, both with fellow friends and with teachers who provide education at the Islamic boarding school. Students emulate the morals taught and demonstrated by teachers in learning and daily activities at the Islamic boarding school. Student morals reflect the character of a santri who imitates his kiay. The role of social media on the morals of class IX students at the Babussalam Modern Islamic Boarding School shows a positive relationship or impact where social media is used appropriately to support the learning process, especially those related to the formation of students' character who have morals, starting by showing lectures and videos about good behavior. with all of God's creatures. In this way, students are able to use social media as a means of learning and having good morals where teachers also provide direct examples of how to apply good morals. The use of social media can be directed towards positive activities and this attracts students to learn.